Determination of toral antioxidant capacity of saliva in sickle cell anemic patients - A cross-sectional study - Sudhindra Baliga; Minal Chaudhary; Sham S Bhat; Poonam Bhatiya; Nilima Thosar; Pooja Bhansali (Wolters Kluwer Medknow Publications, 2017)
Background: Sickle cell anemia is a congenital hemoglobinopathy characterized by deformed red blood cells. Oxidative stress plays an important role in the pathophysiology of sickle cell anaemia as it destroys free radicals, and thereby depleting the protective mechanisms such as antioxidants in serum. These antioxidants are essential to protect against harmful oxidation-reduction reactions preventing oxidative damage to the cells. Aim: To evaluate and compare the Total Antioxidant Capacity (TAC) of serum and saliva in sickle cell anemia patients. Materials and Methods: A total of 150 children aged 4-12 yrs were selected and divided into two equal groups: Children suffering from sickle cell anemia and healthy controls. Blood and saliva samples were collected aseptically from both groups and were subjected to phosphomolybdenum method. Absorbance was read spectrophotometrically at 695 nm. The concentration of total antioxidants was obtained by plotting absorbance of the test against the standard graph. Results: TAC levels in serum (0.29±0.19) and saliva (0.29±0.14) of sickle cell anaemic patients was reduced when compared with serum (0.32+ 0.18) and saliva (0.33+ 0.16) of the healthy children. The correlation between levels of TAC in saliva and serum was found to be statistically significant in sickle cell anaemic patients. Conclusion: A significant correlation of the TAC was found in saliva and serum of the patients with SCA suggests that saliva could be used as a non invasive alternative for assessing the antioxidant status in patients with SCA.